2022
DOI: 10.1186/s12888-022-03964-6
|View full text |Cite|
|
Sign up to set email alerts
|

Trends, correlates, and disease patterns of sedative-hypnotic use among elderly persons in Taiwan

Abstract: Objective The population-based National Health Insurance database was adopted to investigate the prevalence, correlates, and disease patterns of sedative-hypnotic use in elderly persons in Taiwan. Methods The National Health Research Institutes provided a database of 1,000,000 random subjects in the National Health Insurance program. We adopted this sample of subjects who were older than 65 years from 1997 to 2005 and examined the proportions of ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In addition, higher prevalence is noted among institutionalized residents versus community-dwelling older adults (25)(26)(27). Despite such challenges, several studies (24,25,28,29) found increasing trends up until 2005 or 2015, with more recent investigations showing declining patterns of use over the past decade for benzodiazepines (26,(30)(31)(32), psychotropics (27,33), and atropinic medications (34).…”
Section: University Of Ljubljana Faculty Of Pharmacy 1000 Ljubljana S...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, higher prevalence is noted among institutionalized residents versus community-dwelling older adults (25)(26)(27). Despite such challenges, several studies (24,25,28,29) found increasing trends up until 2005 or 2015, with more recent investigations showing declining patterns of use over the past decade for benzodiazepines (26,(30)(31)(32), psychotropics (27,33), and atropinic medications (34).…”
Section: University Of Ljubljana Faculty Of Pharmacy 1000 Ljubljana S...mentioning
confidence: 99%
“…Few studies have examined the trends in overall sedative load, but several studies have focused on specific groups of sedative medications (26)(27)(28)(29)(30)(31)33). These studies generally reported increasing trends until around 2010, followed by decreasing trends in the subsequent decade.…”
Section: Trends In Sedative Loadmentioning
confidence: 99%
“…Hypnotic drugs are one of the most commonly prescribed classes of psychotropic drugs [ 3 ], consisting of traditional benzodiazepines (BZDs) and new generational nonbenzodiazepines (non-BZDs), colloquially as Z-drugs [ 4 ]. The traditional BZDs including diazepam, lorazepam, triazolam, oxazepam, and midazolam, are widely used in the treatment of psychiatric disorders, while prescriptions of the non-BZDs, including zaleplon, zopiclone, and zolpidem, have been greatly promoted over BZDs, because of their superior safety as a short-acting hypnotic drug.…”
Section: Introductionmentioning
confidence: 99%
“…Following the publication of the original article [ 1 ], the authors identified that the funding note was incorrect. The correct funding note is given below.…”
mentioning
confidence: 99%